Shock Advertising and Audience Response: Qualitative Content Analysis of Comments on Billboard Promotion of the Movie Aku Harus Mati on Platform Threads - Nur Cholis; Rika Amijayanti (Asian Journal of Management Analytics, 2026)
This study analyzes audience responses to the large outdoor billboard promotion of the film Aku Harus Mati, which triggered public discussion on Threads. Using qualitative content analysis with thematic coding, this study examines 98 public comments from two Threads posts by @dr.piprim and @dr.bobbyjantung. The findings indicate that audience responses were dominated by discomfort, perceptions of psychological triggering, ethical criticism, concern for children and vulnerable groups, negative virality, and calls for rejection. The study argues that high digital engagement does not always indicate promotional effectiveness, especially when public attention is accompanied by moral criticism and reputational risk. The findings contribute to discussions on shock advertising, advertising ethics, and audience reception in digital marketing communication.